RO 90-7501 Enhances TLR3 and RLR Agonist Induced Antiviral Response - Guo, Fang (Public Library of Science, 2012)
Recognition of virus infection by innate pattern recognition receptors (PRRs), including membrane-associated toll-like receptors (TLR) and cytoplasmic RIG-I-like receptors (RLR), activates cascades of signal transduction pathways leading to production of type I interferons (IFN) and proinflammatory cytokines that orchestrate the elimination of the viruses. Although it has been demonstrated that PRR-mediated innate immunity plays an essential role in defending virus from infection, it also occasionally results in overwhelming production of proinflammatory cytokines that cause severe inflammation, blood vessel leakage and tissue damage. In our efforts to identify small molecules that selectively enhance PRR-mediated antiviral, but not the detrimental inflammatory response, we discovered a compound, RO 90–7501 (‘2’-(4-Aminophenyl)-[2,5′-bi-1H-benzimidazol]-5-amine), that significantly promoted both TLR3 and RLR ligand-induced IFN-β gene expression and antiviral response, most likely via selective activation of p38 mitogen-activated protein kinase (MAPK) pathway. Our results thus imply that pharmacological modulation of PRR signal transduction pathways in favor of the induction of a beneficial antiviral response can be a novel therapeutic strategy.